BIOMARKERS IDENTIFICATION AND THERAPY TARGET IN MACROPHAGE OF ATHEROSCLEROSIS: SYSTEMATIC REVIEW - KURNIATI, NENG FISHERI; MUHAMMAD, HUBBI NASHRULLAH; PRASESTI, GAYUK KALIH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Macrophages are known to play an important role in the initiation and progression of atherosclerosis; however, the molecular signaling pathways in macrophages that are responsible for plaque rupture have not been fully identified. This study aims to identify biomarkers and therapy targets in macrophages in atherosclerotic conditions by systematic review. Research procedure of systematic reviews using the PRISMA protocol. The search engine used in this study is PubMed, with the keywords ([macrophage] AND atherosclerosis) AND (signaling pathway OR signaling pathway), the reference application used is Zotero to screen clinical articles. There were 689 articles identified and 11 clinical articles in inclusion criteria were obtained. The identification resulted in 30 biomarkers associated with macrophages in atherosclerotic conditions. The proposed biomarkers of atherosclerosis are interleukin (IL)-1β and IL-18. The proposed potential therapy targets for atherosclerosis are LOX-1 and schematic images of biomarkers in atherosclerotic plaques.